1996
DOI: 10.1021/ja9620043
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Coupled Oxidation of Heme by an Active Site Variant of Horse Heart Myoglobin

Abstract: The coupled oxidation of protoheme IX at the active sites of heme proteins exposed to ascorbate in the presence of dioxygen has been known for over 65 years and is related to the catalytic conversion of protoheme IX to biliverdin by the enzyme heme oxygenase. The present report demonstrates that replacement of two residues present in the distal heme pocket of horse heart myoglobin (Mb), Val67 and Val68, with alanine and serine, respectively, increases the efficiency of coupled oxidation in the active site of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 40 publications
(37 reference statements)
2
42
0
Order By: Relevance
“…Hence, the fact that the oxidation of heme by HO and by the coupled oxidation process need O 2 and reducing equivalents and proceed via the formation of the same intermediates (meso-hydroxyheme and verdoheme), suggested that the mechanisms of these processes may have been the same. Consequently, the coupled oxidation process has been used to model the process of heme oxidation conducted by the enzyme heme oxygenase [122,125,[127][128][129][130][131][132][133][134][135]. As will be discussed in more detail below, however, recent work has demonstrated that the two processes differ fundamentally in the nature in which the oxidant is generated [136,137].…”
Section: Heme Hydroxylation Mechanism: a Synthesis Of Current Understmentioning
confidence: 99%
“…Hence, the fact that the oxidation of heme by HO and by the coupled oxidation process need O 2 and reducing equivalents and proceed via the formation of the same intermediates (meso-hydroxyheme and verdoheme), suggested that the mechanisms of these processes may have been the same. Consequently, the coupled oxidation process has been used to model the process of heme oxidation conducted by the enzyme heme oxygenase [122,125,[127][128][129][130][131][132][133][134][135]. As will be discussed in more detail below, however, recent work has demonstrated that the two processes differ fundamentally in the nature in which the oxidant is generated [136,137].…”
Section: Heme Hydroxylation Mechanism: a Synthesis Of Current Understmentioning
confidence: 99%
“…Myoglobin (Mb) is a single-chain protein of 153 amino acids containing a heme (iron-containing porphyrin) group in the center which is found in mammalian skeleton and muscle tissues. Mb functions physiologically in the storage of oxygen and in the enhancement of the rate of oxygen diffusion, and has catalytic activity for H 2 O 2 decomposition similar to horseradish peroxidase [17,18]. It is an ideal model molecule for the study of electron transfer reactions of heme proteins and also for biosensing and biocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Myoglobin (Mb) is a single-chain protein of 153 amino acids, containing a heme (iron-containing porphyrin) group in the center. Mb is found in mammalian skeleton and muscle tissues, which functions in the storage of oxygen and in the enhancement of the rate of oxygen diffusion [1,2]. But the electron transfer of Mb is very slow on conventional electrodes because of protein adsorption and subsequent passivation of the electrodes surface.…”
Section: Introductionmentioning
confidence: 99%